Assessing the role of the universal addition of CT thorax to CT abdomen and pelvis in the COVID era. A retrospective multicentre cohort study - Brennan, Christopher Anthony (BJR Open, 2020)
OBJECTIVE: The SARS-CoV2 infection is associated with high mortality for individuals who undergo emergency surgery. The United Kingdom surgical associations and Colleges of Surgeons collectively recommended the addition of CT Thorax to all emergency CT abdomen/pelvis imaging in order to help identify possible COVID-19 patients. Early identification of these patients would lead to optimal treatment strategies for the patient and protection for staff members. However, an extension of CT would be associated with increased irradiation doses for the patient, and its diagnostic relevance was unclear. METHODS: This was a retrospective observational review looking at all surgical admissions that required a CT Thorax/Abdomen/Pelvis across 7 weeks during the COVID-19 pandemic, across four Scottish Hospitals. CT thorax investigations (of non-surgical patients) were also re-assessed by a single radiologist to assess the extent of pathology identified at the lung bases (and therefore would be included in a standard CT abdomen and pelvis). RESULTS: Of 216 patients identified who had a CT thorax/Abdomen/Pelvis during the timeframe, 5 were diagnosed with COVID-19. During this timeframe, 77 patients underwent solely CT thorax. Across the entire cohort, 98% of COVID pathology was identified at the lung bases. The estimated sensitivity and specificity of CT thorax was 60 and 86.4% respectively. CONCLUSIONS: In a region with relatively low prevalence of SARS-COV2 infection, inclusion of CT Thorax in surgical admission imaging does not significantly contribute to identification and management of SARS-COV2 patients. We therefore suggest that imaging the lung bases can be sufficient to raise clinical suspicion of COVID-19. ADVANCES IN KNOWLEDGE: This paper adds further evidence to that from other single UK centres that the addition of CT chest for all patients does not yield any further diagnostic information regarding coronavirus. Additionally, rapid SARS-CoV-2 testing in the UK (which is currently widely available) further demonstrates that inclusion of the entire chest during CT examination of the acute abdomen is not required.